Underwater Noise Monitoring with Real-Time and Low-Cost Systems, (The CORMA Experience) - Paolo Diviacco; Antonio Nadali; Massimiliano Iurcev; Mihai Burca; Rodrigo Carbajales; Matteo Gangale; Alessandro Busato; Fabio Brunetti; Lorenzo Grio; Alberto Viola; Nikolas Potleca (Journal of Marine Science and Engineering, 2021)
Marine life can be severely affected by anthropogenic underwater noise. This latter increased proportionally to the rise of human activities such as maritime traffic, marine civil engineering works, oil- and gas-related activities or offshore wind farms; so much so that, currently, it can be considered a threat to the environment. Assessing underwater noise requires quite some investments both in personnel and instrumentation. If this is affordable by several governmental and scientific organizations, this cannot be extended straightforwardly to all research initiatives or to developing countries. In addition, time and geographic coverage of monitoring can also be significantly limited by the costs of multiple installations. We explore the possibility to use a solution based on off-the-shelf and low-cost technologies combined with a scalable infrastructure developed with open-source tools only. The perspective to avoid proprietary solutions allows great flexibility in extending the current paradigm toward real-time transmission, processing, and web-based data access. Our solution has been deployed at sea in November 2020 and is providing data continuously ever since. First results from the analysis of these data allowed us to highlight several interesting abiotic and anthropogenic temporal patterns.